The plastic waste problem- a pledge for volunteer activities - Kolstee, Yolande G. (Kurdistan Journal of Applied Research, 2017)
In this explorative study, an overview of up to date data on plastic waste is given. Different methods of handling the plastic waste problem are described. The focus lies on volunteering.In order to get a picture of the plastic waste problem, a non-exhaustive overview is given of recent scientific and policy reports in paragraph 2. In paragraph 3 the guidelines of the UNEP and ISWA report on Global Waste Management is described. Other sources emphasize the importance of additional measurements. Those are e.g. self-organising volunteer activities in (higher-) education and volunteer cleaning up activities, respectively described in paragraph 4 and 5. In a small sample investigation to the motives for taken part in cleaning-up activities, undertaken in the Netherlands, Europe, two hypotheses were tested ‘cleaning-up is a token activity’ and ‘taking part in cleaning-up activities promotes environmental-friendly behaviour’.In paragraph 6 the method of the inquiry is described and in paragraph 7 we see from there some evidence for an expanding involvement with pro-environmental behaviour as a result from beach cleaning-up activities. In paragraph 8 we conclude that the need for involvement with the plastic waste problem of all and on all levels, is necessary. The contribution of volunteer activities like self-organizing groups in Universities or cleaning-up projects, seems to be an important factor in behavioural change to tackle the problem of plastic waste.